Micro‐RNAs as critical regulators of matrix metalloproteinases in cancer. Issue 11 (21st August 2018) - Noruzi, Somaye; Azizian, Mitra; Mohammadi, Rezvan; Hosseini, Seyede Atefe; Rashidi, Bahman; Mohamadi, Yousef; Nesaei, Abolfazl; Seiri, Parvaneh; Sahebkar, Amirhossein; Salarinia, Reza; Aghdam, Arad Mobasher; Mirzaei, Hamed
Abstract: Metastasis is known to be one of the important factors associated with cancer‐related deaths worldwide. Several cellular and molecular targets are involved in the metastasis process. Among these targets, matrix metalloproteinases (MMPs) play central roles in promoting cancer metastasis. MMPs could contribute toward tumor growth, angiogenesis, migration, and invasion via degradation of the extracellular matrix and activation of pre‐pro–growth factors. Therefore, identification of various cellular and molecular pathways that affect MMPs could contribute toward a better understanding of the metastatic pathways involved in various tumors. Micro‐RNAs are important targets that could affect MMPs. Multiple lines of evidence have indicated that deregulation of various micro‐RNAs, including miR‐9, Let‐7, miR‐10b, and miR‐15b, affects metastasis of tumor cells via targeting MMPs.